Effectiveness of vonoprazan-based regimens compared with proton pump inhibitor-based regimens as first-line Helicobacter pylori agents - Kakiuchi, Toshihiko (Frontiers in Pharmacology, 2023)
In this study, we compared the success rate of eradicating H. pylori in adults and children using vonoprazan (VPZ)-based H. pylori regimens to that of proton pump inhibitors (PPIs). In Japan, the success rate of a VPZ-based regimen as first-line therapy was lower in children than in adults. Compared with adults, children around puberty have higher CYP2C19 and CYP3A4 enzymatic activity to metabolize PPIs and VPZ. Further, children generally have shorter intestinal transit times than adults and may absorb antibiotics to a lesser extent. When comparing success rates of pediatric and adult eradication therapy using VPZ, it is very important to maintain a higher intragastric pH with sufficient gastric acid suppression to maintain H. pylori in a replicating state and amoxicillin and clarithromycin in the intestinal tract for as long as possible by reducing diarrhea as a side effect. Based on the above, it is reasonable that VPZ, which can suppress stomach acids more strongly than PPI, is a more relevant H. pylori eradication therapy.